Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3892/ol.2012.676
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous bilateral Paget’s disease of the breast: A case report

Abstract: Abstract. Synchronous bilateral Paget's disease of the nipple is extremely rare. In the present study, we report a case of synchronous bilateral Paget's disease in a 45-year-old woman who had a medical history of gastric cancer. The patient presented with a 6-month history of eczema and itching in both nipples. Mammography and ultrasonography did not reveal any mass lesions in the bilateral breast, and computed tomography and bone scintigraphy showed no site of distant metastasis. The patient was scheduled for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For bilateral PD the limited data are controversial. Sahoo et al [ 4 ] connected the PD of its patient to an underlying lobular CIS because of the immunohistochemical profile; Xie et al [ 10 ] found no underlying tumor, whereas the patients of Anderson [ 11 ] and Franceschini et al [ 12 ] as well as our patient had underlying ductal carcinomas.…”
Section: Discussionmentioning
confidence: 76%
“…For bilateral PD the limited data are controversial. Sahoo et al [ 4 ] connected the PD of its patient to an underlying lobular CIS because of the immunohistochemical profile; Xie et al [ 10 ] found no underlying tumor, whereas the patients of Anderson [ 11 ] and Franceschini et al [ 12 ] as well as our patient had underlying ductal carcinomas.…”
Section: Discussionmentioning
confidence: 76%
“…There are extremely few reports of bilateral synchronous Paget's disease without underlying breast cancer in literature. 2 13 …”
Section: Discussionmentioning
confidence: 99%
“… 1 Bilateral eczematous lesions of NAC are more often due to benign etiology with Paget's disease reported extremely rarely. 2 We discuss an extremely rare case with calciphylaxis due to underlying liver disease and sole breast involvement as benign NAC ulceration. Few cases of breast parenchymal involvement by calciphylaxis in end-stage renal disease patients have been reported; however, to the best of our knowledge, there are no cases due to underlying liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…There are many conditions that may mimic PD of the breast such as psoriasis, contact dermatitis, erosive adenomatosis of the nipple, intraductal papilloma, nipple adenoma, basal cell carcinoma, Bowen's disease, malignant melanoma, and Toker cell hyperplasia [ 23 ]. It is commonly mistaken with benign dermatological diseases of the nipple, particularly, dermatitis [ 24 ]. PD of the breast can be distinguished from a locally advanced breast cancer presenting as satellite skin nodules [ 10 ].…”
Section: Discussionmentioning
confidence: 99%